2015
DOI: 10.1002/chem.201501334
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Artificial Nucleobases by E. coli Purine Nucleoside Phosphorylase versus its Ser90Ala Mutant in the Synthesis of Base‐Modified Nucleosides

Abstract: A wide range of natural purine analogues was used as probe to assess the mechanism of recognition by the wild-type (WT) E. coli purine nucleoside phosphorylase (PNP) versus its Ser90Ala mutant. The results were analyzed from viewpoint of the role of the Ser90 residue and the structural features of the bases. It was found that the Ser90 residue of the PNP 1) plays an important role in the binding and activation of 8-aza-7-deazapurines in the synthesis of their nucleosides, 2) participates in the binding of α-D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 60 publications
3
20
0
Order By: Relevance
“…Practically irreversible phosphorolysis of 7-Me-Guo and 7-Me-dGuo in the presence of PNP ensures the quantitative transformation of starting nucleosides to anomerically pure Rib-p and dRib-p. Rib-p and dRib-p are obtained with 74-96 % yields after isolation and purification (48-81 % overall, taking into account the stage of preparation of the initial 7-Me-Guo/7-Me-dGuo). The structure of the obtained compounds was confirmed by 1 H, 13 C, 31 P NMR, and mass-spectroscopy.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Practically irreversible phosphorolysis of 7-Me-Guo and 7-Me-dGuo in the presence of PNP ensures the quantitative transformation of starting nucleosides to anomerically pure Rib-p and dRib-p. Rib-p and dRib-p are obtained with 74-96 % yields after isolation and purification (48-81 % overall, taking into account the stage of preparation of the initial 7-Me-Guo/7-Me-dGuo). The structure of the obtained compounds was confirmed by 1 H, 13 C, 31 P NMR, and mass-spectroscopy.…”
Section: Discussionmentioning
confidence: 84%
“…[20] Signals of protons at 5.68 (dd, 1H, J 1,2 = 4.9 Hz, J H-P = 4.4 Hz, H1) and 5.84 (ddd, 1H, J 1,2a = 6.6 Hz, J 1,2b = 1.4 Hz, J H-P = 6.1 Hz, H1) demonstrated characteristic J H,P couplings typical for Rib-p and dRib-p 1 H-NMR spectra. Moreover, J C,P coupling constants were observed in 13 C-NMR spectra. The purity of Rib-p and dRib-p was also confirmed via enzymatic reaction of the obtained substances with allopurinol or adenine in the presence of PNP (see supplementary materials).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…[42,43] . In the case of flex-bases 3 and 4,H PLC monitoring showed that the glycosylation reactions were more effective than in the case of 1 ( Figure S2 and Ta ble 1, entries [15][16][17][18][19][20][21]. Only one isomer,t he N1-glycosylated product 3a or 4a was formed, even if the enzyme concentration was reduced tenfold (entries [19][20][21].…”
Section: Enzymatic Glycosylation Mediated By Llndtmentioning
confidence: 97%
“…[11,12] NPs have been reportedt oa ccept modified bases as well as unnatural glycosyldonors. [6][7][8][9][13][14][15] NDTs( EC 2.4.2.6) catalyzet he transfer of 2-deoxyriboseb etween purine and pyrimidine bases. [16] TwoN DT types have been defined based on their substrate specificity:N DT-I (also named PTD), which is specific for purines, [17] and NDT-II, which accepts either purine or pyrimidine but has as trong preference for 2'-deoxyribosyl-pyrimidinea st he donor substrate.…”
mentioning
confidence: 99%